1992
DOI: 10.1016/0014-5793(92)81092-z
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species are involved in the activation of cellular phospholipase A2

Abstract: Vrntldatc (V) porcnliukd (4. lo IO-fold) tlrc ;trtir.;ltion of ccllr~lur phorphalipwz A: (PLA:) induscd by tl202 (H). ZI pharbol crkr (T), u Cur'4onaphorc (A) and oplrank~d xynwsw in macruphtiycr. V+H induced in inkul eelIs the uclivution and wztnrlacurian of PLA~~trntl pratcin kinrlc C (PKC) to the plnrmn nwmbnnc. V+tI ;ind V+T+A induced slrony chcmilumincrrcnrc (CL) which WIIL ubrogied by II ~rpccGc NADPH oxid;lr inhibitor diphcnylcnr iudonium (DPI). DPI mrwkcdly riuppmscd lhc sinrulalion of PLA: by V+T+A ;r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
56
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 22 publications
4
56
0
Order By: Relevance
“…The role played by ROS in inhibiting phosphatases has been described previously. When phosphatases are downregulated, PLA2 remains activated due to the presence of an attached phosphate group not removed by the weak enzyme [94]. Furthermore, phosphorylation and a subsequent activation of PLA2 may be achieved by a cascade of events involving ROS stimulating PTK, which will act upon PKC, leading to P-PLA2 and sperm membrane degradation [50,95,96] (see Fig.…”
Section: Acrosome Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role played by ROS in inhibiting phosphatases has been described previously. When phosphatases are downregulated, PLA2 remains activated due to the presence of an attached phosphate group not removed by the weak enzyme [94]. Furthermore, phosphorylation and a subsequent activation of PLA2 may be achieved by a cascade of events involving ROS stimulating PTK, which will act upon PKC, leading to P-PLA2 and sperm membrane degradation [50,95,96] (see Fig.…”
Section: Acrosome Reactionmentioning
confidence: 99%
“…Griveau et al [86] indicated that treatment of capacitated spermatozoa with potassium superoxide resulted in an oxidative insult to the plasma membrane by O 2 − and a subsequent de-esterification of the membrane phospholipids [86]. Activation of PLA2 leads to increased fluidity of the sperm plasma membrane, which means it plays an important function in the regulation of AR and contributes to successful sperm-oocyte fusion [86,94]. Fig.…”
Section: Acrosome Reactionmentioning
confidence: 99%
“…In phagocytic cells such as macrophages, activation of the NADPH oxidase pathway initiates an intracellular ROS signaling pathway that can amplify the production of proinflammatory cytokines, such as TNF␣ (22). In neutrophils, NADPH oxidase is an important source of ROS generation for both oxidative burst (23) and cell signaling pathways (24). Recent work suggests that intracellular ROS mediate ␤-amyloid peptide-induced microglial activation, whereas inhibition of intracellular ROS results in the reduction of ␤-amyloidinduced NF-B activation and lowered interleukin-1␤ expression (25).…”
mentioning
confidence: 99%
“…addition, ROI regulate inositol 1,4,S-trisphosphate (InsP,) production in human B lymphocytes [6j, activation of mitogen-activated-protein kinase in NIH 3T3 cells [7], and phospholipase A2 in macrophages [8]. InsP, production is abolished by preincubation with protein-tyrosine kinase (PTK) inhibitor but not with protein kinase C inhibitor [8], which suggests that PTK enzymes are involved in mediating ROI roles.…”
mentioning
confidence: 99%
“…InsP, production is abolished by preincubation with protein-tyrosine kinase (PTK) inhibitor but not with protein kinase C inhibitor [8], which suggests that PTK enzymes are involved in mediating ROI roles. Hydrogen peroxide can activate ~7 2 '~~ in human B cells [9] and peripheral blood lymphocytes [ 101.…”
mentioning
confidence: 99%